2008
DOI: 10.1007/s00384-008-0442-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transanal endoscopic microsurgery on functional outcome and quality of life

Abstract: Introduction Transanal endoscopic microsurgery (TEM) is a minimal invasive technique for local excision of rectal tumours. The procedure is performed via a rectoscope with a diametre of 4 cm. The aim of this prospective study was to assess both functional outcome and quality of life after TEM. Patients and methods Between 2004 and 2006, 47 patients were studied prior to and at least 6 months after TEM. Demographics, operative details and post-operative complications were recorded. Functional outcome was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 26 publications
4
40
1
6
Order By: Relevance
“…We were unable to clarify these doubts because we received no reply to our request from the respective study authors. In all, 21 studies met the inclusion criteria for a total of 2,077 patients: 11 ESD series [11][12][13][14][15][16][17][18][19][20][21] totaling 536 patients, and 10 TEM series [2,[22][23][24][25][26][27][28][29][30], totaling 1,541 patients. …”
Section: Resultsmentioning
confidence: 99%
“…We were unable to clarify these doubts because we received no reply to our request from the respective study authors. In all, 21 studies met the inclusion criteria for a total of 2,077 patients: 11 ESD series [11][12][13][14][15][16][17][18][19][20][21] totaling 536 patients, and 10 TEM series [2,[22][23][24][25][26][27][28][29][30], totaling 1,541 patients. …”
Section: Resultsmentioning
confidence: 99%
“…Resection of rectum by conventional surgery, in case of unfavourable pathology after TEM, is an option used in our institute successfully. TEM has been shown not to have any long-term effect on anorectal function or quality of life (QOL) [18,19]. The ageing population in the UK is presenting us with management dilemmas for early rectal cancer when conventional surgical resection has been shown to have significantly higher risks of post-operative morbidity and mortality in the elderly [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our patients had a mean age of 71, and a significant proportion (48 %) had an ASA of III or IV. The evidence on selection criteria for TEM is especially poor, and the literature shows that larger tumours (>3 cm) in combination with submucosal invasion depth are significant predictive factors for locoregional failure after TEM for T1 rectal cancer [19,21]. The evidence for oncological safety of TEM for T2 tumours is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated by endorectal ultrasound that partial lesions of the internal anal sphincter can occur in up to 29% of patients 1 . Other studies have shown no significant changes in incontinence scores or in quality of life questionnaires in the long term evaluation 21,22 . Despite the fact that our patients were not submitted to sphincter evaluation with ultrasound, no anal incontinence was referred in this initial experience.…”
Section: Discussionmentioning
confidence: 99%